Integrating Intercultural Communicative Competence into English Language Teaching in Nepalese Community Schools (Journal of NELTA Gandaki, 2025)
This study explores the integration of intercultural aspects into English language teaching at the Basic Level in Nepal. Focusing on teachers’ perceptions, practices, challenges, and needs, it aims to identify strategies to enhance Intercultural Communicative Competence (ICC) in classrooms defined by linguistic and cultural diversity. A qualitative research approach was employed, applying semi-structured interviews guided by a set of interview guidelines. Participants included English teachers from community schools in Chitwan, with about a decade of teaching experience at the Basic Level (Grade 6-8). The findings reveal that classrooms in Nepal are highly multicultural, with students from diverse linguistic and cultural backgrounds. Teachers adopt strategies such as storytelling, role-playing, and ICT-based tools to facilitate intercultural learning. However, challenges such as insufficient resources, lack of training, curriculum rigidity, and time constraints hinder effective integration of intercultural content. Despite these barriers, teachers emphasize the importance of intercultural communicative competence in preparing students for global engagement and fostering respect for cultural diversity. This study highlights the need for curriculum reforms to incorporate more context-sensitive intercultural content and improve flexibility. It also highlights the significance of formal training for teachers, with an emphasis on intercultural pedagogy and collaboration with native speakers. These findings invite interculturally friendly policy and curriculum design. Future research should investigate students’ perspectives on intercultural learning and evaluate the impact of tailored interventions on their intercultural communicative competence.